Museums & Galleries : Displaying Korea's Past and Future. - Jackson, Ben (Korea essentials., 2013)
The history of Korean museums goes back more than 100 years, to the opening of the Jesil Bangmulgwan in 1909. There are now 11 national museums in provincial cities throughout Korea, unified by the hub that is Seoul's iconic National Museum of Korea, completed in 2005, while the large number of regional, university, art, specialized and other museums continues to rise. Korea's galleries emerged one by one with the advent of ""modernity, "" the flourishing of modern art and the development of the economy, introducing many Korean and international artists and playing an important role in developin.